CONSTRUCTION AND PERFORMANCE TESTING OF AXIAL MOVABLE WIND TURBINE - Rufinus Nainggolan; Berta Br. Ginting; Nobert Sitorus; Joko Sutrisno; Suadi; Baringin Sibarani (Journal of Information Technology, computer science and Electrical Engineering, 2025)
In this article is conducted research to harness wind energy which is generated by a truck that is running on the public road and highway. To take advantage of wind energy of the moving truck is designed a axial movable wind turbine in accordance with the size of the current truck. The purpose of this research is to construct and testing the performance of the designed axial movable wind turbine which is based on the optimum blades size. Number of the blades are six pieces and diameter of the blades are 0.35 m. To test the wind turbine that have been assembled, it is used loads on the wind turbine, respectively, 8 watts and 25 watts. The wind turbine that will be tested is installed on a mini truck. Furthermore, the mini truck runs at speeds up to 80 km/h. This research has succeeded to design and testing a prototype of axial movable wind turbine and the designed wind turbine can resulted electrical energy about 3.5 watts with the load 25 watt bulb. The designed axial movable wind turbine can be installed in the truck by further improving some components of the resulted prototype of the axial movable wind turbine.